Energization and spoken language production: Evidence from progressive supranuclear palsy. (October 2018) - Barker, Megan S.; Nelson, Nicole L.; O'Sullivan, John D.; Adam, Robert; Robinson, Gail A.
Abstract: Energization is the process of initiating and sustaining a response over time. It has been described as one of three key "supervisory" attentional control processes associated with the frontal lobes. Attentional mechanisms, such as energization, are critical for a range of cognitive functions, such as spontaneous speech and other higher-order tasks. We aimed to investigate the process of energization in a case series of patients with progressive supranuclear palsy (PSP). Patients with a diagnosis of PSP ( N = 5), patient controls with a neurodegenerative condition (Alzheimer's disease N = 3, frontotemporal dementia N = 2) and healthy older adult controls ( N = 30) were assessed on a standard neuropsychological battery, including executive tasks and standard attention and language tests. Energization was investigated using word fluency tasks, samples of spontaneous speech and an experimental button-pressing concentration task. Response rates for the word fluency, spontaneous speech and concentration tasks were separated into time periods, in order to compare response rates at different points across the tasks (e.g., first 15 s vs. last 45 s in a 60 s task). Four PSP patients showed a clear response pattern indicative of a decrease in energization. Healthy and patient controls remained consistent in their responding over time. Understanding how these underlying processes are impaired in PSP can ultimately inform intervention and management strategies, and has theoretical implications for models of spoken language production. Highlights: Patients with progressive supranuclear palsy are unable to maintain consistent responding. This pattern is characteristic of an energization impairment. Deficient energization observed on an experimental task, word fluency and in spontaneous speech. Energization plays a key role in the generation of ideas for spontaneous speech.